Calmodulins from Schistosoma mansoni: Biochemical analysis and interaction with IQ-motifs from voltage-gated calcium channels. (September 2018) - Thomas, Charlotte M.; Timson, David J.
Graphical abstract: Highlights: S. mansoni has two calmodulins with very similar biochemical properties. Both proteins interact with Ca 2+, Mn 2+, Cd 2+, Fe 2+ and Pb 2+ ions. Both interact with an IQ-motif from the voltage-gated calcium channel SmCav 1B. The affinity of this interaction is slightly increased by calcium ions. Chlorpromazine and trifluoperazine antagonise these interactions. Abstract: The trematode Schistosoma mansoni is a causative agent of schistosomiasis, the second most common parasitic disease of humans after malaria. Calcium homeostasis and calcium-mediated signalling pathways are of particular interest in this species. The drug of choice for treating schistosomiasis, praziquantel, disrupts the regulation of calcium uptake and there is interest in exploiting calcium-mediated processes for future drug discovery. Calmodulin is a calcium sensing protein, present in most eukaryotes. It is a critical regulator of processes as diverse as muscle contraction, cell division and, partly through interaction with voltage-gated calcium channels, intra-cellular calcium concentrations. S. mansoni expresses two highly similar calmodulins – SmCaM1 and SmCaM2. Both proteins interact with calcium, manganese, cadmium (II), iron (II) and lead ions in native gel electrophoresis. These ions also cause conformational changes in the proteins resulting in the exposure of a more hydrophobic surface (as demonstrated by anilinonaphthalene-8-sulfonate fluorescence assays). The proteins are primarily dimeric in the absence of calcium ions, but monomeric in the presence of this ion. Both SmCaM1 and SmCaM2 interact with a peptide corresponding to an IQ-motif derived from the α-subunit of the voltage-gated calcium channel SmCav 1B (residues 1923–1945). Both proteins bound with slightly higher affinity in the presence of calcium ions. However, there was no difference between the affinities of the two proteins for the peptide. This interaction could be antagonised by chlorpromazine and trifluoperazine, but not praziquantel or thiamylal. Interestingly no interaction could be detected with the other three IQ-motifs identified in S. mansoni voltage-gated ion calcium channels.